2010
DOI: 10.1007/s10620-010-1257-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Analogue Can Improve the Long-Term Prognosis of Patients with Hepatitis B Virus Infection-Associated Acute on Chronic Liver Failure

Abstract: These data indicated that nucleoside analogue treatment did not improve the short-term prognosis of patients with HBV-associated ACLF although it was efficacious and safe in the management of HBV DNA levels. Intriguingly and importantly, continuous nucleoside analogue treatment can significantly reduce the rate of recurrence, which might be indicative of the further benefit of long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 32 publications
4
62
0
Order By: Relevance
“…Both hepatic and non-hepatic insults could occur as acute precipitating events and dip the stable cirrhotic patients or those with mild decompensation in to the syndrome of ACLF [15]. Even though the data is sparse, studies from the West suggest non-hepatic insults like acute variceal bleed and non-hepatotropic infections and sepsis as the acute precipitating events and data from South East Asia and the Indian subcontinent supports hepatic injury as the major acute event [2][3][4][5][6][7][8][9][10][11][12]. Jalan et al had suggested that non hepatic insults like gastrointestinal bleeding or sepsis may start a cascade of events that culminate in end-organ dysfunction and liver failure in a patient with stable cirrhosis [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both hepatic and non-hepatic insults could occur as acute precipitating events and dip the stable cirrhotic patients or those with mild decompensation in to the syndrome of ACLF [15]. Even though the data is sparse, studies from the West suggest non-hepatic insults like acute variceal bleed and non-hepatotropic infections and sepsis as the acute precipitating events and data from South East Asia and the Indian subcontinent supports hepatic injury as the major acute event [2][3][4][5][6][7][8][9][10][11][12]. Jalan et al had suggested that non hepatic insults like gastrointestinal bleeding or sepsis may start a cascade of events that culminate in end-organ dysfunction and liver failure in a patient with stable cirrhosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Though data from Southeast Asia have implicated the acute flare of HBV as the cause of ACLF [5,6], studies from the Indian subcontinent have suggested acute viral hepatitis (AVH) because of HEV as a recognized trigger of hepatic decompensation in patients with cirrhosis [7][8][9][10][11][12]. In one of the Indian studies, 50% of patients with cirrhosis and rapid decompensation had HEV RNA positivity in contrast to 19 and 10% HEV RNA positivity in patients with cirrhosis and chronic decompensation and patients with cirrhosis without decompensation, respectively [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the journal, Cui and colleagues reported a single-center experience among 104 chronic hepatitis B patients presented with acute-on-chronic liver failure in Chengdu, China [14]. This is by far one of the biggest reports in this clinical condition.…”
mentioning
confidence: 99%
“…Owing to the shortage of cadaveric donor organ, a prognostic model is essential to time the living-related liver transplantation. Cui and colleagues found that the only factors associated with better survival were younger age, higher cholinesterase level, and lower Model of End-Stage Liver Disease (MELD) score [14]. The MELD score of the survivors was 23 ± 4 and that of the non-survivors was 25 ± 6.…”
mentioning
confidence: 99%